Pengaruh Kecukupan Konsumsi Zink dengan Kejadian Stunting: Studi Literatur - Septiana Purwandini; Dominikus Raditya Atmaka (Universitas Airlangga, 2023)
Background: Stunting is a condition where under five children' height not in accordance with standard according to age. This condition is caused by inadequate nutritional intake during the First 1000 Days of Life. Stunting in long term period can cause a decrease in productivity due to cognitive decline and brain development. One of the important nutritional intake to prevent stunting is zinc. Objectives: The purpose of this study was to determine the effect of zinc on the incidence of stunting in Indonesia. Methods: The research method in this article is a literature review on Google Scholar database with the keywords